2016
DOI: 10.1126/science.aaf5529
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic ocean circulation and abrupt climate change during the last glaciation

Abstract: The most recent ice age was characterized by rapid and hemispherically 11

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
345
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 347 publications
(377 citation statements)
references
References 55 publications
30
345
0
2
Order By: Relevance
“…1), the Cariaco Basin reflectance influenced by movements of the Intertropical Convergence Zone (43), and the Bermuda Rise calcium concentration influenced by the Atlantic Meridional Overturning Circulation (44) (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…1), the Cariaco Basin reflectance influenced by movements of the Intertropical Convergence Zone (43), and the Bermuda Rise calcium concentration influenced by the Atlantic Meridional Overturning Circulation (44) (Fig. 4).…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations in West Antarctic Ice Sheet Divide (WAIS) ice core (Buizert et al, 2015) have demonstrated the north-to-south-directed transfer of the abrupt changes with Greenland warmings leading Antarctic coolings; the associated heat transfer is argued to be modulated by the Atlantic Meridional Overturning Circulation rather than by the atmosphere (Henry et al, 2016). Although the origin of the DO events is not yet elucidated, the North Atlantic changes still remain the drivers of those observed over Eurasia.…”
Section: Discussionmentioning
confidence: 99%
“…Ice cores nevertheless provide much more information than on temperature and dust concentration only, as they release records of numerous components of the climate system, isotope values of the transported water vapor, mineral aerosols and greenhouse gas concentrations, chemical elements, etc., which show different origins and transport patterns to the high-latitude ice sheets. Such richness in proxies allows comparisons with other records of millennial-scale variability preserved in both marine (Henry et al, 2016) and terrestrial deposits, as well as in other ice cores (Barbante et al, 2006;Buizert et al, 2015). In this paper, after briefly describing the abrupt changes observed in the very-high-resolution δ 18 O and dust records from NGRIP (NGRIP, 2004), we compare the dust particle sedimentation rates over Europe and China as expressed in key loess sequences (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It has long been recognized that during stadials and glacial maxima marine ice-sheets and icy fresh water masses may have been associated with diminished heat transport to the high latitude North Atlantic (Broecker and Denton 1989;Raymo et al 1990;Imbrie et al 1992;Henry et al 2016). In addition, each major ice sheet collapse was associated with the release of, abundant icebergs that drifted southward and melted primarily in the subpolar Atlantic (Ruddiman 1977;Heinrich 1988;Broecker et al 1992; McManus et al , 1999Hemming 2004;Naafs et al 2013).…”
Section: Glacial/interglacial Deep Atlantic Water Distributionmentioning
confidence: 99%